2023
DOI: 10.1108/ijbm-10-2022-0475
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of the financial wellbeing of individuals in an emerging economy: an empirical study

Abstract: PurposeThe current study aims to identify the impact of financial literacy, financial risk-tolerance, financial socialization, financial stress, socio-demographic factors and financial behavior on the individual financial wellbeing residing in India's National Capital Region (NCR) region. Understanding financial wellbeing is crucial as it helps individuals understand personal finance better and develop a more favorable financial attitude. The information can depict individuals' financial skills, knowledge and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 68 publications
0
9
0
Order By: Relevance
“…The survey responses were obtained between August and November 2022. Further, due to budget and time constraints, convenient sampling is more appropriate for this study, as used by a similar study (Kumar et al , 2023). A total number of 426 questionnaires were distributed.…”
Section: Methodsmentioning
confidence: 99%
“…The survey responses were obtained between August and November 2022. Further, due to budget and time constraints, convenient sampling is more appropriate for this study, as used by a similar study (Kumar et al , 2023). A total number of 426 questionnaires were distributed.…”
Section: Methodsmentioning
confidence: 99%
“…They found that people with higher-income levels displayed better behavior than other income groups (Joo and Grable, 2004). In addition, financial education guides in enhancing FB (Kumar et al. , 2023) to reduce FS and improve FIS (Joo and Grable, 2004).…”
Section: Review Of Literaturementioning
confidence: 99%
“…Hair et al (2019) state that the CA and composite reliability (CR) values lie between 0.7 and 0.95. In Table 2, the values of CA (0.717-0.878) and CR (0.750-0.917) lie between the recommended value and confirmed data validity and reliability (Kumar et al, 2023a(Kumar et al, , 2023b.…”
Section: Assessment Of Measurement Modelmentioning
confidence: 56%